2017
DOI: 10.3201/eid2304.161743
|View full text |Cite
|
Sign up to set email alerts
|

Ebola Virus RNA in Semen from an HIV-Positive Survivor of Ebola

Abstract: Ebola virus is known to persist in semen of male survivors of Ebola virus disease (EVD). However, maximum duration of, or risk factors for, virus persistence are unknown. We report an EVD survivor with preexisting HIV infection, whose semen was positive for Ebola virus RNA 565 days after recovery from EVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 6 publications
0
20
0
Order By: Relevance
“…Reported sequelae include arthralgia, cardiac valvulopathy, parotid gland inflammation, peripheral paresthesia or dysesthesia, and gastrointestinal motility disorders 10 14 . Semen may contain detectable EBOV RNA for more than 500 days following recovery, and EBOV RNA has been detected in breast milk of a subclinically infected mother 15 , 16 . Replicating EBOV has been isolated from the cerebrospinal fluid of an EVD survivor suffering a disease relapse and from the aqueous humor of the eye of another survivor 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Reported sequelae include arthralgia, cardiac valvulopathy, parotid gland inflammation, peripheral paresthesia or dysesthesia, and gastrointestinal motility disorders 10 14 . Semen may contain detectable EBOV RNA for more than 500 days following recovery, and EBOV RNA has been detected in breast milk of a subclinically infected mother 15 , 16 . Replicating EBOV has been isolated from the cerebrospinal fluid of an EVD survivor suffering a disease relapse and from the aqueous humor of the eye of another survivor 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Deen et al [ 4 ] detected EBOV RNA in the semen of 11 (26%) of 43 men sampled at 7 to 9 months after EVD onset, whereas Sow et al [ 9 ] in Guinea found evidence of EBOV RNA in semen collected from only 2 of 31 (7%) men within a similar time period. There are even fewer data regarding the presence of EBOV RNA in the semen of EVD survivors further out from their disease onset, although cases of detectable viral RNA in the semen of men 407 to 565 days after Ebola Treatment Unit (ETU) release have been reported [ 2 , 7 , 10 , 11 ].…”
mentioning
confidence: 99%
“…There are significant public safety implications associated with EBOV persistence in immune-privileged sites [11]. Besides ocular fluid, it has been reported that EBOV has been detected in semen 18.5 months after discharge from the Ebola Treatment Unit [12]. Sexual transmission of EBOV 470 and 179 days after symptom onset has been confirmed in cases in Guinea and Liberia, respectively [13,14].…”
Section: Persistence Of Ebov In Ocular Fluid and Other Immune-privilegementioning
confidence: 99%